Habits of using social media and the internet in psoriasis patients - Melek Aslan Kayıran; Ayşe Serap Karadağ; İlteriş Oğuz Topal; Esra Adışen; Sevilay Kılıç; Nuray Keskin; Asude Kara Polat; Bengü Çevirgen Cemil; Mualla Polat; Oğuz Yılmaz; Hilal Ayvaz; Filiz Topaloğlu Demir; et al. (Mattioli1885, 2022)
Introduction: Psoriasis significantly affects the patients' quality of life, which often leads patients to seek online information about this disease. Objectives: To explore the habits of patients with psoriasis related to their use of SM and the internet to obtain information about their disease. Methods: 1,520 patients completed the survey and the Dermatology Life Quality Index (DLQI) questionnaire. The Psoriasis Area Severity Index scores (PASI) and clinical data of the patients were recorded by their physicians. Results: Of the 1,114 patients that reported using social media (SM) and the internet, 48.38% regularly and 31.14% sometimes resorted to obtain information about psoriasis. The use of SM and the internet for psoriasis was statistically significantly higher among young people (p=0.000), those with university or higher education (p=0.009), higher DLQI (p=0.000) and PASI (p=0.011) scores, facial (p=0.050), scalp (p=0.032), hand (p=0.048), genital (p=0.001) and inverse (p=0.000) involvement, and arthralgia/arthritis (p=0.006). The participants mostly used the Google (86%) and Facebook (%41). More than half the participants (62.8%) expected dermatologists to inform society that psoriasis is not contagious. Conclusion: The internet and SM being widely available and offering substantial information to be easily accessed make it very attractive for patients to use these platforms to investigate diseases, including psoriasis. If what is presented on SM conflicts with what the physician says, patients mostly trust the latter, but at the same time, they tend not to share the results of their online inquiries with their physicians.